“M-Auto” The Augmented Reality-Based (AR) Learning Media Application for the Finite-State Automata (FA) Reduction Subject of Language and Automata Theory Courses - Fajar Ananda Saputra; F Ti Ayyu Sayyidul Laily; Dimas Prasetyo Buseri; Imro’aturrozaniyah Imro’aturrozaniyah; Kartika Candra Kirana (Universitas Negeri Malang, 2020)
AbstractA proper learning process should contain innovative, amusing, challenging, and motivating aspects. It should be able to provide an opportunity for the students to develop their creativity and independence based on their interests and talent. Less interesting and tedious classroom learning activity indicates the factor of the students’ learning interest degradation, for example as in the language and automata theory and finite-state automata reduction subject. The current research aims to aid language and automata theory in a learning activity to be easier to acquire. With the Augmented Reality-based learning media, the researcher hopes that the students can develop their understanding and their interest in a learning activity, especially for finite-state automata subjects. The subject of the current research is the Augmented Reality-based application as the learning media for language and automata theory and finite-state automata material. The researcher employs several research methodologies such as literature review, library research, and questionnaire to support the current research. The application is designed according to system development that consists of problem identification, appropriateness study, need analysis, concept designing, content designing, script designing, graphic designing, system production, and system examination. The result of the current research is the AR-based learning media application for the finite-state automata reduction subject of language and automata theory. Keywords: Learning Media, Finite-State Automata Reduction, Augmented Reality